The experience of traditional nature management as the basis for the environmental culture formation - Gorbunova, Sofiya (Building Peace through Heritage - World Forum to Change through Dialogue, Florence, 13-15 March 2020 : abstract book of the forum)
The crisis of overconsumption violates the interconnected unity of the ecological, social and economic sustainability: excessive consumption provokes production growth, which leads to increasing resource costs, including nonrenewable ones. In addition, an increase in production and consumption entails an increase in waste, which damages the environment and reduces the quality of life. The way out may be the conversion to a different type of production and consumption, which suggests new principles of human interaction with nature. Globally speaking, this means the formation of environmental culture as a basic characteristic of human and society in the XXI century. Mankind has accumulated rich experience of coexistence with nature. In traditional forms of nature management ecosystems remain highly productive and, providing a person with everything necessary, do not lose their sustainability. In this case, environmental culture is part of ethnic culture. The experience of Siberian indigenous peoples shows that traditional nature management made it possible to preserve unique natural ecosystems in a relatively pristine state. In traditional cultures, nature is understood as a living being, and a person uses as many resources as necessary for life support. But this principle of human interaction with the environment is not dominant in modern civilization. Thus, the positive experience of traditional nature management must be applied in the development of educational strategies, programs, projects, involving thereby indigenous peoples in the formation of the global environmental culture of modern civilization